Cold rolled tungsten (W) plates and foils: Evolution of the tensile properties and their indication towards deformation mechanisms. (January 2018) - Bonk, Simon; Hoffmann, Jan; Hoffmann, Andreas; Reiser, Jens
Abstract: This paper is the second part of our series on ultrafine-grained (UFG) tungsten produced by cold rolling. The aim of this paper is to determine tensile properties, with a focus on uniform elongation and flow stress, and to identify the mechanism of plastic deformation in cold rolled tungsten plates and foils. For this purpose, five plates have been rolled out of a single sintered compact with increasing degrees of deformation, which enables the analysis of mechanical properties with changing microstructure without influence from the chemical composition. Uniaxial tensile tests have been performed in the range of room temperature to 800 °C. The tensile curves show a clear trend of increased strength for finer microstructures and simultaneously evolving room temperature ductility in the low temperature regime for cold rolled plates. The thinnest foil (100 μm) behaves uniquely by forming a plateau in the stress-strain curve, which hints at a change in the deformation mechanism. Analyzing the temperature and grain size dependence of the flow stress reveals that the bulk plasticity is still controlled by screw dislocations and further suggests a change in the dislocation-grain boundary interactions from blocking at low homologous temperatures to absorbing at elevated temperatures. A fracture analysis of cold rolled tungsten foils confirms a plastic deformation prior to fracture and reveals a steady transition from brittle towards lamellar fracture for the highly deformed tungsten foils. Graphical abstract: Highlights: Five plates have been rolled out of a single sintered ingot. The tensile properties in the range of RT to 800 °C have been determined. A change of deformation mechanism has been identified in UFG tungsten. Bulk plasticity is still controlled by screw dislocations. A change in the dislocation-grain boundary interactions is suggested.